Outcome of trabeculectomy with 5-fluorouracil using releasable suture technique in a Nigerian tertiary hospital (2011)
BACKGROUND: Trabeculectomy has undergone a series of modifications in recent times most of which are aimed at improving the efficacy of the procedure while reducing complications. The use of releasable sutures is one of such modifications. OBJECTIVE: To assess the efficacy and complications associated with the use of releasable sutures and 5- Fluorouracil(5-FU) in trabeculectomy among indigenous African patients with primary open angle glaucoma. METHODS: This was a chart review of 22 eyes of 17 patients diagnosed with primary open angle glaucoma. All the eyes included in the review had trabeculectomy with 5-Fluorouracil using releasable suture technique with postoperative clinic follow- up visit for a minimum period of 72 weeks. Information sought included patient’s demographics, preoperative antiglaucoma medications, pre- and post- operative intraocular pressure, and associated complications. RESULTS: There were 17(13 M, 4 F) patients with 22 eye surgeries. Their mean age was 49.8 ± 9.3 years. The mean preoperative intraocular pressure was 27.7 ± 5.9 mmHg. The intraocular pressure on the first post-operative day was 10.6 ± 11.1 mmHg. The mean pressure before the removal of the releasable suture was 14.1 ± 10.8 mmHg and after removal was 6.0 ± 7.2 mmHg, (p < 0.0001). The mean intraocular pressure at 72 weeks of follow up was 16.9 ± 5.6 mmHg. A qualified success rate of 81.8% was achieved in terms of intraocular pressure control. There were two eyes complicated by blebitis and an eye complicated by malignant glaucoma. CONCLUSION: The use of releasable suture in trabeculectomy helped in maintaining the intraocular pressure at a lower level in the early postoperative period and in reducing postoperative shallowing of the anterior chamber. The procedure appears to be associated with some sight- threatening complications such as endophthalmitis.